Análisis Económico del Derecho Penal. Entre lo irreal y lo eficiente - Oporto Gamero, Johann Efraín (2023)
In this article, the author explains the importance of including the Economic Analysis of Law in Criminal Law, so it fulfills its purposes efficiently and reduce the social cost. The price of crime derives from punishment and detection.